A systematic review of novel physiological adaptations in the evolutionary origin of bird flight (2022)
Movement is a fundamental characteristic of animal life, where flying animals encounter a highly energy-demanding form of locomotion but a very advantageous one, only four animal groups during life evolution have evolved the ability to fly, birds being one of them. Flight has affected all aspects of bird biology being closely related the origin of the group with the evolution of fly in them, so a preliminary approach was done by a systematic review searching the physiological adaptations that have explained the evolutionary origin of bird flight from research and review articles from 2000 to 2022, searching the novelties in the study of flight evolution, using the PRISMA-EcoEvo methodology in six databases, identifying 68 adaptations in total where 38 correspond to biomechanics, eight (8) genomics, six (6) metabolic rate, and 16 from systemic. Identifying the importance of a holistic approach to understanding the origin of bird flight and supporting the idea that the explanation with only the musculoskeletal system is not enough.